Energy levels, transition rates and lifetimes for Li-like ions with Z ≤ 10 in the 1s2s(3S)3ℓ states. (August 2015) - Santos, J P; Marques, J P; Martins, M C; Indelicato, P; Benis, E P; Zouros, T J M; Parente, F
Synopsis: Energy levels, transition rates and lifetimes for Li-like ions with Z ≤ 10 in the 1 s 2 s ( 3 S )3ℓ states were calculated using the Dirac-Fock approach.